2019
DOI: 10.1002/yea.3399
|View full text |Cite
|
Sign up to set email alerts
|

SNF1 controls the glycolytic flux and mitochondrial respiration

Abstract: The switch between mitochondrial respiration and fermentation as the main ATP production pathway through an increase glycolytic flux is known as the Crabtree effect. The elucidation of the molecular mechanism of the Crabtree effect may have important applications in ethanol production and lay the groundwork for the Warburg effect, which is essential in the molecular etiology of cancer. A key piece in this mechanism could be Snf1p, which is a protein that participates in the nutritional response including gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…It is important to note that the reductions observed in intracellular ATP levels in snf1∆ cells in the presence of glucose were overlooked in previous biochemical analyses, again demonstrating the usefulness of QUEEN-based ATP imaging. A recent study showed that the deletion of SNF1 decreased glycolytic flux in cells cultured in 1% glucose ( Martinez-Ortiz et al, 2019 ), which supports the novel function of the Snf1 complex.…”
Section: Discussionmentioning
confidence: 74%
“…It is important to note that the reductions observed in intracellular ATP levels in snf1∆ cells in the presence of glucose were overlooked in previous biochemical analyses, again demonstrating the usefulness of QUEEN-based ATP imaging. A recent study showed that the deletion of SNF1 decreased glycolytic flux in cells cultured in 1% glucose ( Martinez-Ortiz et al, 2019 ), which supports the novel function of the Snf1 complex.…”
Section: Discussionmentioning
confidence: 74%
“…In yeast, SNF1 controls glycolytic flux and mitochondrial respiration in a glucose-dependent manner. At 1% glucose, a concentration which we used in M2 medium in our studies with P. anserina, ScSNF1 sustains glycolytic flux and increases respiration (Martinez-Ortiz et al, 2019). Such a function of PaSNF1 in the PaClpP background appears to be not possible because, as revealed by the metabolome analysis, glycolytic flux seems to be impaired in the PaClpP deletion strain leading to the accumulation of C6 sugars and depletion of C3 carbohydrates and because complex I-and complex II-dependent respiration is impaired (Knuppertz and Osiewacz, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to determine a mechanism by which NuA4 may regulate mitochondrial morphology and volume. We first focused our attention on the AMPK/Snf1 and PKA-Msn2/Msn4 axis as they have both been implicated in mitochondrial dynamics [32,[69][70][71][72]. Snf1 is a key kinase in yeast metabolic signalling [27].…”
Section: Mitochondrial Elongation In Eaf1δ Cells Can Be Partially Reversed Upon Deletion Of Bcy1mentioning
confidence: 99%